CYBERVIOLENCE AGAINST TEACHERS AND ITS EFFECTS ON EMOTIONAL WELL-BEING AND JOB PERFORMANCE - Pereira-Hernández, María Luisa; González-Torres, Arturo; López, Pavel David Ulises Avendaño (Veredas do Direito, 2025)
This exploratory-descriptive quantitative study analyses student cyberviolence against secondary school teachers in Sinaloa, Mexico, using a questionnaire administered to 959 educators that examined sociodemographic characteristics, use of digital platforms, experiences of victimisation, and emotional responses. A total of 77% of survey participants acknowledged having heard of coworkers who experienced forms of cyber victimization, such as cyberbullying, provocation, digital harassment, identity theft, the peculiar circulation of insulting material, and AI-generated manipulations. These forms of cyber victimization result in: substantial work-related stress, a range of disturbing psychological and emotional elements such as anxiety, depression, and phobic disorders, decreased productivity in teaching, and thoughts about leaving the profession. Research shows that this occurs at a systemic level with regard to gender and access to formal education. This evidence compels digital safety education organizations to develop and implement educational frameworks that integrate digital and social-emotional learning skills, and to develop frameworks that build safe, ethical, and nonviolent educational ecosystems.